Hak Prerogatif Presiden Menerbitkan Peraturan Pemerintah Pengganti UndangUndang Dengan Dasar Kegentingan Memaksa - Panggabean, Pilipi; Lestari, Maria Maya; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the prerogatives of the President of the Republic of Indonesia is to issue a Government Regulation in Lieu of Law (Perppu). Article 22 of the 1945 Constitution explains that